PELATIHAN METODE APPLIED BEHAVIORAL ANALYSIS (ABA) DALAM MENANGANI ANAK BERKEBUTUHAN KHUSUS BAGI GURU SD GUGUS III SEKACAMATAN CIAWI BOGOR - Nurmawati, Nurmawati; Ithriyah, Siti; Fadliansyah, Fadliansyah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Disorders experienced by children are certainly very unpleasant, especially for parents, teachers and families because there are special limitations that are different from normal children, so parents and teachers need to provide special therapy to abnormal children which of course leads to better. Each therapy has advantages and disadvantages, for example: biomedical therapy focuses more on minimizing hyper behavior so that children can be calm. Occupational therapy helps children train the muscles of the body and legs to be strong and balanced right and left. Teacch that emphasizes children to be able to work purposefully in their community. Sensory integration therapy teaches children how to train the balance of the right and left brain so that they develop in a balanced way. Sone-rise has a main principle, namely following